Features of observation of political police bodies for «politically unreliable» persons in 1867–1917 (on the example of Kursk province) - K. A. Zarubina (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the system of monitoring «politically unreliable» persons in Russia in 1867–1917. The relevance of the topic under consideration is due to the need to study regional aspects for a comprehensive study of this issue. To this end, some aspects of the activities of the political police bodies performing the functions of political observation (on the example of the Kursk province) have been studied, conclusions have been drawn about the effectiveness of the implementation of observation measures in countering the development of the revolutionary situation in the country.